Multinational evaluation of clinical decision-making in the treatment and management of mild-to-moderate ulcerative colitis. (3rd April 2022) - Dignass, Axel U.; Paridaens, Kristine; Al Awadhi, Sameer; Begun, Jakob; Cheon, Jae Hee; Fullarton, John R.; Louis, Edouard; Magro, Fernando; Marquez, Juan Ricardo; Moschen, Alexander R.; Narula, Neeraj; Rydzewska, Grazyna; et al.
Abstract: Objectives: To understand current thinking and clinical decision-making in the treatment and management of patients with mild-to-moderate ulcerative colitis (UC). Methods: This multinational, survey-based study was conducted in 2021. Two meetings were held, involving 11 IBD specialists, that used a series of questions and discussion to identify all factors possibly related to the management of UC. The importance of identified factors was assessed using an online questionnaire covering three scenarios – active disease, remission and patient empowerment. Each factor was scored on a scale of 0 (very-unimportant) to 100 (very-important) within each scenario, by a separate group of healthcare professionals working in IBD. Results: A total of 157 individual factors were identified by the 11 IBD specialists and scored in the three scenarios by 56 respondents (52; 93% specialist gastroenterologists) from Europe and North America (25; 45%), South America (19; 34%) and the Middle East, Asia and Australia (12; 21%). For all scenarios, factors related to educating patients regarding UC and its treatment and understanding of patient goals ranked highest, ahead of clinical considerations regarding disease activity and treatment history. Setting realistic short-term treatment targets was a key consideration. 5-ASA optimisation and use of faecal calprotectin monitoring were core strategies across the three scenarios tested. Support for patients during longer-term management of their disease, starting from initial flare, was an important recurring theme. Conclusion: The current management approach for mild-to-moderate UC was found to be guided primarily by the patient's perspectives and goals, alongside assessment of their medical and disease history.